Crystalline thieno[3, 2-b]thiophene-dioxide-diyl bridged molecular gyrotops as fluorescent dielectric materials. Issue 26 (15th June 2021) - Hayashi, Daiki; Inagaki, Yusuke; Setaka, Wataru
Abstract : Fluorescent dielectric materials that show solid-state fluorescence and dielectric relaxation in the crystalline state were realized using thienothiophene-dioxide-bridged macrocage compounds. Abstract : Fluorescent dielectric materials that show solid-state fluorescence and dielectric relaxation in the crystalline state were realized using crystals of thienothiophene-dioxide-bridged macrocage compounds C14TTO2, C18TTO2 and C22TTO2, in which the first number indicates the length of the alkyl chains in the cage. In these molecules, the fluorophore can rotate even in the crystalline state because the fluorophore is encased in the macrocage frame. Therefore, they are called molecular gyrotops. The rotational dynamics of the fluorophore in the crystalline state were observed by temperature-dependent dielectric relaxation, and the fluorophore was found to be static in C14TTO2, while restricted and facile rotation was observed for C18TTO2 and C22TTO2, respectively. The solid-state fluorescence quantum yield decreased with the increasing alkyl chain length, indicating that the fluorescence intensity clearly depends on the dynamics of the fluorophore.